2021
DOI: 10.1109/jsyst.2020.3026233
|View full text |Cite
|
Sign up to set email alerts
|

Joint Energy and Reserve Scheduling of a Wind Power Producer in a Peer-to-Peer Mechanism

Abstract: This paper proposes a risk constrained decision making problem for wind power producers (WPPs) in a competitive environment. In this problem, the WPP copts to maximize its likely profit whereas aggregators want to minimize their payments. So, this bi-level problem is converted to a single level one. Then, the WPP offers proper prices to the aggregators to attract them to supply their demand. Also, these aggregators can procure reserve for the WPP to compensate its uncertainties. Therefore, through a peer-to-pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Each agent either buys (+) or sells (−) power and flexibility in each time interval. This is ensured using the binary variable v, as shown in Equations ( 10)- (12).…”
Section: Optimization Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Each agent either buys (+) or sells (−) power and flexibility in each time interval. This is ensured using the binary variable v, as shown in Equations ( 10)- (12).…”
Section: Optimization Problemmentioning
confidence: 99%
“…Another study in ref. [12] develops a risk‐constrained joint energy and reserve trading to assist a wind power plant in competing against its peers to attract customers. A CVaR approach is applied to hedge the risks of uncertain resources in the mentioned P2P trading setup.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, P2P model was implemented in [31] using smart features of consortium blockchain for power transactions and contract management in microgrid. To handle uncertainties in WPPs, a P2P trading model was proposed in [32] in order to manage mutual contract for energy transactions. P2P energy trading for prosumer community based on blockchain technologies was proposed in [33] considering uniform price and double auction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Through P2P direct transactions, WPP can offset part of the energy deviation and maximize its interests. H. Rashidizadeh-Kermani et al (Rashidizadeh-Kermani et al, 2020) explored that WPP purchased reserves from energy storage aggregators on the P2P trading floor to compensate for the volatility of wind power, and at the same time introduced conditional value at risk (CVaR) to hedge the randomness of wind energy. Previous work has shown that prosumers take crucial roles in P2P trading.…”
Section: Introductionmentioning
confidence: 99%